Impact of climate change on medicinal and aromatic plants: Review - DAS, MANISH; JAIN, VANITA; MALHOTRA, S K (The Indian Journal of Agricultural Sciences, 2016)
There has been worldwide changes in seasonal patterns, weather events, temperature ranges, and other related phenomena and all have been analyzed in partial, reported and attributed to global climate change. The negative impacts of climate change will become much more intense and frequent in the futureâ€”particularly if environmentally destructive human activities continue unabated, warned categorically by a number of experts in a wide range of scientific disciplines and interests. Medicinal and aromatic plants (MAPs) are not immune to the effects of climate change like all other living members of the biosphere. Clear signals are coming on climate change impact which is causing noticeable effects on the lifecycles and distributions of the worldâ€™s vegetation, including wild MAPs across the world. This in turn causing some MAPs endemic to geographic regions or ecosystems which could put them at risk and are particularly vulnerable to climate change. Such serious issues and challenges are a continuous concern with regard to the survival and genetic integrity of some MAPs and are being discussed within various forum and platform. Further, such issues of climate change will definitely pose a more prominent or immediate threat to MAP species than other threats, however, scientists do not know whether climate change has the potential to exert increasing pressuresÂ upon MAP species and populations. Climate change impact may have a tremendous possible effect on MAPs particularly significant due to their value within traditional systems of medicine and as economically useful plants. At this stage, the future effects of climate change are largely uncertain more so with MAPs, but current evidence suggests that these phenomena are having an impact on MAPs and that there are some potential threats worthy of concern and discussion.